2020
DOI: 10.9745/ghsp-d-19-00317
|View full text |Cite
|
Sign up to set email alerts
|

Coaching Intensity, Adherence to Essential Birth Practices, and Health Outcomes in the BetterBirth Trial in Uttar Pradesh, India

Abstract: Frequent coaching was associated with increased adherence to evidence-based essential birth practices among birth attendants but not with improved maternal and perinatal health outcomes in the BetterBirth Trial, which assessed the impact of a complex intervention to implement the World Health Organization's Safe Childbirth Checklist. To promote sustainable behavior change, future coaching-based interventions may need to explore cost-effective, feasible mechanisms for providing more frequent coaching delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…These findings are significant given other large-scale clinical quality improvement initiatives in Uttar Pradesh that find that high costs and sustained investments are critical to ensuring changes in clinical and non-clinical staff practices. 27 This study provides evidence that a light-touch, spread approach may improve outcomes beyond PCMC outcomes if appropriate strategies are identified in similar facilities.…”
Section: Discussionmentioning
confidence: 87%
“…These findings are significant given other large-scale clinical quality improvement initiatives in Uttar Pradesh that find that high costs and sustained investments are critical to ensuring changes in clinical and non-clinical staff practices. 27 This study provides evidence that a light-touch, spread approach may improve outcomes beyond PCMC outcomes if appropriate strategies are identified in similar facilities.…”
Section: Discussionmentioning
confidence: 87%
“…Fifty-four supervision approaches demonstrated improvements in HRH outputs (95%), of which 36 cited improved skills, knowledge, or attitudes. Some studies demonstrated results at several levels of Bloom’s taxonomy of learning outcomes [ 50 ], from testing individual HCW knowledge and comprehension of health areas or tasks [ 11 , 51 53 ] to measuring the application of specific clinical tasks and adherence to standards of care [ 11 13 , 26 , 28 , 54 ]. Improved attitudes documented by the studies included improved job satisfaction, commitment, and conscientiousness [ 33 ]; increased awareness of the importance of posting facility job aids [ 55 ]; increased recognition and support [ 31 ], and attitudes toward patients [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent large-scale studies in Uttar Pradesh have shown both the potential to change some common practices among both clinical and non-clinical staff, and highlighted the high cost and long-term investments needed to effect those changes [18,19]. The Quality Improvement (QI) literature has documented both the sustained effect, and the gradual change and simplification of interventions over time in hospital settings [20].…”
Section: Challengementioning
confidence: 99%
“…The Quality Improvement (QI) literature has documented both the sustained effect, and the gradual change and simplification of interventions over time in hospital settings [20]. Team-based QI interventions demand significant time and resources commitments and so there has been experimentation in many settings with "Light Touch" variations [21][22][23][24]. We conducted a study to see if a lessdemanding Light Touch intervention could produce improvments in person-centered care similar to a fullintensity QI initiative.…”
Section: Challengementioning
confidence: 99%